ODREĐENI ASPEKTI POZICIONIRANJA FOTONAPONSKIH PANELA U AGROVOLTIČNIM APLIKACIJAMA - Kjosevski, Stevan (Journal on Processing and Energy in Agriculture, 2025)
The paper addresses some of the challenges which arise from the contemporary initiatives and efforts to advance in the field of agrivoltaics (Solar and Agriculture Co-Location) applications.Due to the fact that during agrivoltaics applications there is normally a possibility to choose the orientation of photovoltaic panels, a challenge arises: what is their optimum orientation and way of mounting. This paper describes complex methodology employed in the research (literature analysis, photovoltaic installation, one-year measurement of key quantities, data post processing, and analysis).The results received are presented in graphical manner. They tackle basic correlation between the electric power produced in correlation to the orientation of photovoltaic panels, all dependable of the time in the day and period of the year. Based on such results, this paper offers some answers regarding optimal azimuth and tilt angles of photovoltaic panels.The results and discussion may be of help when deciding the position of photovoltaic panels in agrivoltaics applications, but also for small household units in rural environment.